A case report of bilateral ovarian luteinized thecoma with sclerosing peritonitis masquerading as a malignant mass (Indian Journal of Case Reports, 2025)
Luteinized thecoma with sclerosing peritonitis (LTSP) is a very uncommon syndrome, characterized by the presence of single or bilateral ovarian thecomas and peritoneal fibrotic lesions. The disease occurs in young women, and it can lead to peritoneal fibrosis and bowel obstruction. We present the case of an ovarian mass in a 20-year-old woman. Radiologically, the patient had bilateral large, well-defined, heterogeneously enhancing solid mass lesions in the bilateral adnexa. The lesion extends into the lower abdomen, abutting the compressed fat planes. Her serum carcinoembryonic antigen (1.26 ng/mL) was within normal limits, but the cancer antigen 125 (CA125) (882/mL) level was high. Total abdominal hysterectomy with bilateral adnexal mass, along with part of the omentum, was removed. Histopathological diagnosis was LTSP and was confirmed by immunohistochemistry. Postoperatively, the patient was managed conservatively and was kept in follow-up.